Profil Kemampuan Literasi Sains Pada Mata Pelarajan Biologi Peserta Didik MAN 2 Soppeng - Nurhayati B; Abdul Hadis; Dian Dwi Putri Ulan Sari Patongai; Nurul Ilmi R H (Seminar Nasional LP2M UNM, 2022)
Abstrak. This research is a quantitative descriptive study that aims to describe the scientific literacy ability profile of students in biology class X MAN 2 Soppeng, Soppeng district. Data collection techniques were carried out using a biological science literacy instrument which was given to 24 class X students. Data analysis was carried out by conducting a quantitative descriptive analysis. The results showed that the minimum score for students' literacy after the implementation of scientific literacy-based authentic assessment was 73 with a maximum score of 86 and an average score of 78.04. The score categorization shows that 16.7% of students are in the category of very good scientific literacy ability and 50% of other students are in a good category, while for the sufficient category there are 33.3% of students. So it can be concluded that the scientific literacy skills of class X MAN 2 Soppeng students are in a good category. Kata Kunci: Scientific Literacy Ability, Profile, Biology